Survey of fungi causing postharvest rot in seedless grapes in agricultal polo of Juazeiro-BA and Petrolina-PE - Camargo, Rúbia Brito; Peixoto, Ana Rosa; Terao, Daniel; Ono, Elizabeth Orika [UNESP]; Cavalcanti, Leonardo Sousa (My University, 2011)
In Brazil, postharvest diseases caused by pathogenic microorganisms are a major problem that causes damage to around 80% of the total fruit production. In the lower middle São Francisco river valley numerous studies on identification and control of fungal diseases during postharvest of grapes are needed, in order to minimize losses in this step. In this context, bunches of seedless varieties 'Crimson', 'Sonaka'; 'Superior' and 'Thompson' were collected from July to November 2009, in order to identify and quantify the incidence of pathogenic fungi. The grapes were collected on five farms which specialize in the production of table grapes for export, all located in Juazeiro - BA and Petrolina - PE. During this period, 10 samples were taken. In the fruit farm five plants were used for sampling, and removal of two bunches of grapes per plant, totaling 10 bunches per variety. Subsequently, they were sent to the laboratory of Plant Pathology at UNEB/DTCS where they were placed separately in a moist chamber for 48 hours at an average temperature of 23 °C. After this period, isolations of berries and stems in Petri plates containing PDA - potato-dextrose-agar were carried out with 10 repetitions, which were placed on benches under laboratory conditions. From the 8th day on, the presence of Aspergillus niger, Alternaria alternata, Cladosporium herbarum, Lasiodiploidia theobromae was observed, which presented the highest incidence, as well as Rhizopus stolonifer, Penicillium expansum.
Fungos causadores de podridões pós-colheita em uvas apirênicas no pólo agrícola de juazeiro-BA e petrolina-PE
Keywords: Alternaria; Aspergillus; Patology; Phytopathogens